Telemedicine and Smart Working: Recommendations of the European Association of Urology - Rodriguez Socarrás, Moises (Eur Urol, 2020)
CONTEXT: Telemedicine provides remote clinical support using technological tools. It may facilitate health care delivery while reducing unnecessary visits to the clinic. The coronavirus disease 2019 (COVID-19) outbreak has caused an abrupt change in our daily urological practice, converting many of us to be reliant on telehealth. OBJECTIVE: To provide practical recommendations for effective use of technological tools in telemedicine. EVIDENCE ACQUISITION: A Medline-based and gray literature search was conducted through April 2020. We selected the most relevant articles related to “telemedicine” and “smart working” that could provide important information. EVIDENCE SYNTHESIS: Telemedicine refers to the use of electronic information and telecommunications tools to provide remote clinical health care support. Smart working is a model of work that uses new or existing technologies to improve performance. Telemedicine is becoming a useful invaluable tool during and even beyond the COVID-19 pandemic. It is time for us to formalize the place of telemedicine in routine urological practice, and it is our responsibility to adapt and learn about all the tools and possible strategies for their optimal implementation during the pandemic to ensure that the quality of care received by patients and the outcomes of patients and their families are of the highest standard. CONCLUSIONS: Telemedicine facilitates specialized urological clinical support at a distance, solves problems of limitations in mobility, reduces unnecessary visits to clinics, and is useful for reducing the risk of viral transmission in the current COVID-19 outbreak. Furthermore, both personal and societal considerations may favor continued use of telemedicine, even beyond the COVID-19 pandemic. PATIENT SUMMARY: Telemedicine in urology offers specialized remote clinical support to patients, similar to face-to-face visits. It is very useful for reducing unnecessary visits to the clinic, as well as reducing the risk of contagion in the current coronavirus disease 2019 (COVID-19) pandemic.